An Examination of the Role of Social Media in Enhancing Customer Service: A Case Study of Trackers Safari Lodge - Arinaitwe, Micheal (Kabale University, 2025)
The study examined the role of social media in enhancing customer service. a case study of Trackers Safari Lodge following the objectives of the study which were; to find out the role of social media in customer service in the tourism sector, to identify customer service in the tourism sector, and to establish the relationship between social media and customer service in the tourism sector. A descriptive research design was used across a sample of 54 respondents. Data collection tools were questionnaires and interview guides. The results of the study revealed that male respondents dominated the study. Results further revealed the role of social media in the tourism sector which included Customer Interaction and Engagement with 67%, Customer Feedback and Reviews with 50%, and Brand Image and Reputation Management with 82%. The study concluded that the findings from Trackers Safari Lodge provide empirical support for much of the existing literature on the role of social media in the tourism sector. While there are areas for improvement, particularly in managing customer feedback, the overall positive perception of social media's impact on customer service is consistent with established research. This underscores the importance of leveraging social media effectively to enhance customer engagement, manage brand reputation, and drive business success in the tourism industry. The study recommends that Trackers Safari Lodge should develop and implement a comprehensive social media engagement strategy that focuses on personalized communication and timely responses to customer inquiries and feedback. Encourage customers to leave reviews on social media platforms and respond to both positive and negative feedback professionally. Use social media to proactively manage and enhance the brand image and reputation of the business.